Физика высоких энергий и гомологическая алгебра - Малюта, Ю.M.; Обиход, Т.В.; Семенов, В.Н. (Видавничий дім "Академперіодика" НАН України, 2008)
This work is devoted to searches for a new physics beyond the standard model.